(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The article examines the phraseological representation of the concept of “Love” by native speakers of Belarusian and English, which is one of the basic concepts that appear in representatives of various cultures. Attention is focused on the main parameters of the intensity of this feeling. Common features and national features of the cultural image encoded in the internal form of Belarusian and English phraseological units are established. The analysis of phraseological verbalization of the concept “Love” helps to recreate the ethno-cultural image and features of the mentality of Belarusian and English speakers. The results of the research demonstrate that the Belarusian and English phraseological units representated the concept of “Love” are divided into several semantic groups. These groups describe the degree of depth and strength of the feeling, or certain stages of it. For example, phraseological units characterize the origin of love, the highest degree of this feeling, and its completion: to fall in love ‘to fall in love’ – with all one’s heart <and soul> ‘(to love, believe, be proud, etc.) sincere, heartfelt)’ (1 st meaning) – to fall out of love ‘to stop loving’. Linguistic meaning and cultural content of the phraseological units cause their special role in the speaking – to characterize the person’s attitude to the feeling of love and pay attention to the different ways of their display. The national-cultural interpretation of the concept “Love” in phraseology of native speakers of Belarusian and English shows that to imagine the part of their language picture of the world could be exactly through the description of the stereotypes in the inner form of the phraseological units. The conclusions of the article can be used in giving courses in the field of phraseology, cultural linguistics, inter-language communication, theory and practice of translation and compiling of phraseological dictionaries.